Advising Female and Male Student-Athletes: How Gender Differences Affect the Advising Process - Gruber, Carol A. (My University, 1993)
There is much discussion in the advising profession today regarding the special needs of student-athletes. However, the issue of how gender affects the advising process has been a neglected topic. How does being male or female affect the way students behave in academic and athletic settings? How does gender affect self-esteem, expectations for success, stress, and the resulting behavior of student-athlete populations? How do these issues and advisors' own assumptions affect the way they advise students? This paper began a much needed exploration of this important topic.
Keywords: sex/gender